The Evx1/Evx1as gene locus regulates anterior-posterior patterning during gastrulation - Bell, Charles C. (Sci Rep, 2016)
Thousands of sense-antisense mRNA-lncRNA gene pairs occur in the mammalian genome. While there is usually little doubt about the function of the coding transcript, the function of the lncRNA partner is mostly untested. Here we examine the function of the homeotic Evx1-Evx1as gene locus. Expression is tightly co-regulated in posterior mesoderm of mouse embryos and in embryoid bodies. Expression of both genes is enhanced by BMP4 and WNT3A, and reduced by Activin. We generated a suite of deletions in the locus by CRISPR-Cas9 editing. We show EVX1 is a critical downstream effector of BMP4 and WNT3A with respect to patterning of posterior mesoderm. The lncRNA, Evx1as arises from alternative promoters and is difficult to fully abrogate by gene editing or siRNA approaches. Nevertheless, we were able to generate a large 2.6 kb deletion encompassing the shared promoter with Evx1 and multiple additional exons of Evx1as. This led to an identical dorsal-ventral patterning defect to that generated by micro-deletion in the DNA-binding domain of EVX1. Thus, Evx1as has no function independent of EVX1, and is therefore unlikely to act in trans. We predict many antisense lncRNAs have no specific trans function, possibly only regulating the linked coding genes in cis.